2014
DOI: 10.1371/journal.pone.0083472
|View full text |Cite
|
Sign up to set email alerts
|

Global Pharmacogenomics: Distribution of CYP3A5 Polymorphisms and Phenotypes in the Brazilian Population

Abstract: The influence of self-reported “race/color”, geographical origin and genetic ancestry on the distribution of three functional CYP3A5 polymorphisms, their imputed haplotypes and inferred phenotypes was examined in 909 healthy, adult Brazilians, self-identified as White, Brown or Black (“race/color” categories of the Brazilian census). The cohort was genotyped for CYP3A5*3 (rs776746), CYP3A5*6 (rs10264272) and CYP3A5*7 (rs41303343), CYP3A5 haplotypes were imputed and CYP3A5 metabolizer phenotypes were inferred a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 22 publications
3
20
1
4
Order By: Relevance
“…CYP3A5 exhibited metabolic activity comparable to CYP3A4 (∼90%) toward CBZ epoxidation in vitro [40]. The CYP3A5*3 polymorphism is the most common and functionally important across all ethnic populations studied, and there was a statistically significant difference in the variant allele frequency among various populations [18,41]. CYP3A5 seemed to constitute up to 50% of total hepatic CYP3A protein in subjects carrying at least one CYP3A5*1 allele [42,43].…”
Section: Discussionmentioning
confidence: 97%
“…CYP3A5 exhibited metabolic activity comparable to CYP3A4 (∼90%) toward CBZ epoxidation in vitro [40]. The CYP3A5*3 polymorphism is the most common and functionally important across all ethnic populations studied, and there was a statistically significant difference in the variant allele frequency among various populations [18,41]. CYP3A5 seemed to constitute up to 50% of total hepatic CYP3A protein in subjects carrying at least one CYP3A5*1 allele [42,43].…”
Section: Discussionmentioning
confidence: 97%
“…This difference may be due to genetic differences between the primarily Caucasian cohorts from The Netherlands compared with the Brazilian cohort which has strong African ancestry. The Brazilian cohort likely has other important low activity or nonfunctional CYP3A5 variants not present in Caucasians which may confound the analysis [43]. Recently, another group in The Netherlands reported CYP3A4*22 in 101 kidney transplant recipients receiving tacrolimus and found a trend toward reduced tacrolimus clearance but considered the effect too small to be clinically important [44].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted with Chinese patients (Wang et al, 2012) found no significant differences between male and female in both control and case groups regarding the risk of stroke. The difference in results can be explained by the population used in each study, and it is noteworthy to say that the Brazilian population is marked by a high degree of miscegenation (Suarez-Kurtz et al, 2014).…”
Section: Discussionmentioning
confidence: 85%